Pengaruh Kualitas Pelayanan, Keamanan Operasional dan Fasilitas Bandara Terhadap Kepuasan Pelanggan di Bandar Udara Internasional Minangkabau - Milawati Milawati; Nadia Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Customer satisfaction is a critical indicator of airport operational success amid the intensifying competition in the air transportation industry. This study aims to analyze and empirically verify the influence of service quality, operational security, and airport facilities on customer satisfaction at Minangkabau International Airport (BIM). A quantitative approach with a cross-sectional survey design was applied to 228 respondents selected through purposive sampling technique. Data were collected using a structured questionnaire based on a 1–5 Likert scale and analyzed using multiple linear regression via SPSS version 29. The results indicate that all three independent variables have a positive and significant effect on customer satisfaction, both partially and simultaneously. Operational security emerged as the most dominant predictor (β = 0.302), followed by service quality (β = 0.233), and airport facilities (β = 0.194). Simultaneously, the three variables account for 63.9% of the variation in customer satisfaction (R² = 0.639; F = 131.927; p < 0.001). These findings contribute theoretically to the development of satisfaction-based aviation management and serve as a strategic reference for BIM management in establishing sustainable service improvement priorities.